Trauma-induced testicular germ cell tumor in Priangan ram: A histopathological study - Prasaja Aditya Gilang; Wijaya Stevanie Andrea; Windria Sarasati; Septiyani; Hartady Tyagita; Setyowati Endang Yuni; Wicaksana Dwi Nawang (BIO Web of Conferences)
Testicular germ cell tumors (TGCT) are a rare group of neoplasms originating from the uncontrolled growth of germ cells within the testes. These tumors can significantly disrupt reproductive function by interfering with normal spermatogenesis, the process of sperm production. This case report details a unique instance of a TGCT in a young, 2-year-old Priangan ram, initially suspected based on clinical findings of testicular abnormality. Histopathological examination revealed the presence of a seminoma, a specific type of TGCT, encompassing the entire seminiferous tubule, the site of sperm development within the testes. This extensive involvement suggests a potential for substantial disruption of the ram’s fertility. The observed seminoma displayed classic and spermatocyte subtype characteristics, adding complexity to the case. Trauma resulting from ram fighting is suspected as the underlying cause of this TGCT, highlighting a potential environmental factor in the development of these tumors. This report contributes valuable information to the limited body of knowledge surrounding TGCTs, emphasizing the importance of considering these neoplasms in the differential diagnosis of testicular abnormalities and recognizing their potential impact on male reproductive health.